2005
DOI: 10.1038/sj.jp.7211420
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and bacterial sepsis and threshold ROP in preterm very low birth weight neonates

Abstract: Objective: To determine whether an association exists between either fungal or bacterial sepsis and retinopathy of prematurity (ROP).Study Design: Retrospective cohort study on all neonates with birth weight <1500 g admitted to a large Italian third Level Neonatal Intensive Care Unit in the years 1997-2001 and screened for ROP. Univariate analysis and multiple logistic regression were used to detect significant associations with ROP (all grades and threshold) in neonates with birth weight <1000 g (extremely lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 27 publications
2
52
1
1
Order By: Relevance
“…It is possible that the small number of infants with fungemia in our cohort prevented detection of a real relationship between this condition and progression to severe ROP. However, it is also possible that fungal sepsis served as a non-specific marker for sustained severe illness in studies reporting an association between fungemia and ROP, [38][39][40][41] with cumulative illness severity adjusting for this risk in this study.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that the small number of infants with fungemia in our cohort prevented detection of a real relationship between this condition and progression to severe ROP. However, it is also possible that fungal sepsis served as a non-specific marker for sustained severe illness in studies reporting an association between fungemia and ROP, [38][39][40][41] with cumulative illness severity adjusting for this risk in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, seven studies plus an abstract, all retrospective cohort studies, were found by both the authors and were included for analysis in this review. [12][13][14][15][16][17][18]20 The characteristics of these studies are presented in Table 1. There were many similarities and differences in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…All patients included were only ELBW in some studies 12,[15][16][17][18]20 but VLBW and ELBW in others. 13,14 Also, all studies expressed their central tendency and measures of dispersion as mean ± standard deviation except one which expressed it as median and range. 18 In addition, all studies addressed the exposures of SFI alone except some that studied bacterial sepsis in addition to SFI 13,17 and others that studied the effect of race 16 on ROP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations